Contributions to the intelligent design theory from the curricular contents of molecular genetics - Molero Paredes, Tamara Maria (2020)
The study of the complex ultracellular processes of nucleic acids is a subject debated as a scientific argument in favor of Intelligent Design (ID). The objective of this work was to analyze some molecular processes of the nucleic acids that suggest the confirmation of the ID theory, through the technique of documentary content analysis. First, the chemical structure of DNA and the combination of nitrogenous bases reflects that the genetic information of each created being is an original mixture of nitrogenous bases that makes each individual unique in the history of the world. Secondly, by studying the processes of DNA replication and repair, it is observed that each enzyme fulfills its function in a coordinated and organized manner avoiding the occurrence of errors and, should this occur, the cell has had very fine repair mechanisms. that correct these alterations in the best possible way. Third, the process of manufacturing proteins and their highly regulated control involves the participation of enzymes and proteins that work in an organized manner to obtain proteins, some of them unrepeatable, that define the identity of the living being. The final part discusses the impressive and perfect packaging mechanism of nucleic acids. This combination of processes, organization and preparation of special and precise machineries definitely come from a meditated design of a superior being. Finally, a section was written where ideas about the defense of Intelligent Design Theory are exposed.